Matter and manner: A postcolonial reading of Nol Alembong’s The Passing Wind (1991) - Sih, Emmerencia Beh; Kimbeng, Nges Zillah (Research Journal in Advanced Humanities, 2022)
This paper sought to examine the role of Anglophone Cameroonian writers who have had a persistent tendency for political and social commitment and change, in connection to the socio-political events of their society. Initially, Anglophone Cameroon writing was an instrument for celebrating the heroic magnificence of Western figures; later it was used for anti-colonial fight back. Presently, it is being used as an authentic weapon for depicting the postcolonial disillusioned state of the nation and other burning issues. In this paper, an effort is made to examine the way “manner” is used to bring out the blazing “matter[s]” in Cameroon, Africa and the world. In an attempt to examine Nol Alembong’s view, selected poems from his collection titled, The Passing Wind, have been used to bring out tangible issues that have plagued Africa as a whole and Anglophone Cameroon in particular. This article adopts the Socio-Artistic Criticism and Marxism as its theoretical perspectives. This theoretical position is important as it focuses not only on the background from which the poems were written, but also pays close attention to the use of literary and linguistic tools in communicating meaning.